Substrate utilization during exercise performed with and without glucose ingestion in female and male endurance-trained athletes - Riddell, M. C.; Partington, S. L.; Stupka, N.; Armstrong, D.; Rennie, C.; Tarnopolsky, M. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2003)
Compared to males, females oxidize proportionately more fat and less carbohydrate during endurance exercise performed in the fasted state. This study was designed to test the hypothesis that there may also be gender differences in exogenous carbohydrate (CHOexo) oxidation during exercise. Healthy, young males (n = 7) and females (n = 7) each completed 2 exercise trials (90 min cycle ergometry at 60% VO2peak, 1 week apart. Females were eumenorrheic and were tested in the midfollicular phase of their menstrual cycle. Subjects drank intermittently either 8% CHOexo (1 g glucose · kg · h-1) enriched with U-13C glucose or an artificially sweetened placebo during the trial. Whole-body substrate oxidation was determined from RER, urinary urea excretion, and the ratio of 13C:12C in expired gas during the final 60 min of exercise. During the placebo trial, fat oxidation was higher in females than in males (0.42 ± 0.07 vs. 0.32 ± 0.09 g · min-1 · kg LBM-1 × 10-2) at 30 min of exercise (p < .05). When averaged over the final 60 min of exercise, the relative proportions of fat, total carbohydrate, and protein were similar between groups. During CHOexo ingestion, both the ratio of 13C:12C in expired gas (p < .05) and the proportion of energy derived from CHOexo relative to LBM (p < .05) were higher in females compared to males at 75- and 90-min exercise. When averaged over the final 60 min of exercise, the percentage of CHOexo to the total energy contribution tended to be higher in females (14.3 ± 1.2%) than in males (11.2 ± 1.2%; p = .09). The reduction in endogenous CHO oxidation with CHOexo intake was also greater in females (12.9 ± 3.1%) than in males (5.1 ± 2.0%; p = .05). Compared to males, females may oxidize a greater relative proportion of CHOexo during endurance exercise which, in turn, may spare more endogenous fuel. Based on these observations, ingested carbohydrate may be a particularly beneficial source of fuel during endurance exercise for females.